Schistosoma haematobium infection modulates Plasmodium falciparum parasite density and antimalarial antibody responses. (24th February 2020) - Tokplonou, Léonidas; Nouatin, Odilon; Sonon, Paulin; M'po, Grace; Glitho, Sonya; Agniwo, Privat; Gonzalez‐Ortiz, Daniel; Tchégninougbo, Théophile; Ayitchédji, Aurèle; Favier, Benoit; Donadi, Eduardo A.; Milet, Jacqueline; et al.
Abstract: Aims: Schistosomiasis and malaria are endemic in sub‐Saharan Africa where Schistosoma haematobium ( Sh ) and Plasmodium falciparum ( Pf ) coinfections are thus frequent. We explored the effect of Sh infection on antibody responses directed to Pf merozoite antigens and on malaria susceptibility in Beninese children. Methods and results: A total of 268 children were followed during a malaria transmission season. Detection of Pf infection was performed by microscopy and rapid diagnostic tests. Sh infection was determined in urine by microscopy. Antimalarial antibody, cytokine and HLA‐G concentrations were quantified by ELISA. The expression of HLA‐G receptors by immune cells was assessed by flow cytometry. Children infected by Sh had higher concentrations of IgG1 directed to MSP3 and GLURPR0, IgG2 directed to GLURPR0 and IgG3 directed to MSP3, GLURPR0 and GLURPR2 and have lower Pf densities than those uninfected by Sh. No difference in cytokine and HLA‐G concentrations was observed between Sh egg carriers and non‐carriers. Conclusion: Schistosoma haematobium modulates host immune responses directed to Pf antigens. The absence of immune downregulation usually observed during helminth infections is surprising in our study. We hypothesize that the stage of Sh development could partly explain the immune pathways leading to increased antibody levels that favour better control of Pf parasitemia.